Organizational factors on employees' job resources and job performance: A multilevel approach / Michelle Lee Chin Chin - Michelle, Lee Chin Chin (2016)
The purpose of this research was to seek a better understanding of the role of organizational contexts in influencing employees’ job resources and work outcomes. The study was firstly conducted, by using a cross sectional (N= 256 individuals, 44 organizations) and a longitudinal multilevel survey (N= 134 individuals, 28 organizations) in Malaysia, followed by another cross sectional study (N=500, 65 organizations). The findings pointed to the importance of organizational contexts (i.e. organizational climates, organizational culture, and organizational leadership) in the providence of some types of job resources (i.e. personal development, role clarity, work meaningfulness, and performance feedback) to the employees’ work outcomes (personal initiative, job performance, and sleeping problems). The findings also highlighted the different types of job resource functions as significant mediators to employees’ outcomes, which includes job engagement, personal initiative, burnout, health problems, and job performance. The study presented at least three contributions to work psychology. Firstly, different types of organizational contexts resulted in different types of job resources. Secondly, organizational contexts played an important role in increasing employees’ job performance, with job resources as mediators to organizational contexts and job engagement. Thirdly, that it was important to ensure that the organizational contexts are aligned so that the organizational systems become clear for employees to be productive at work. It is hoped that the findings from this research will be of use to higher management within organizations who seek to create employees who are productive and contented so that they are beneficial to organizations.